Pernicious Anaemia Masquerading as Addison’s Disease in an HIV-Infected Woman (Tanzania Medical Journal, 2023)
Pernicious anaemia is a manifestation rarely reported in HIV-infected patients. We report a case of a 35-year-old female with well-controlled HIV-infection, who presented with skin hyperpigmentation, pancytopenia and productive cough which mimick Addison’s disease. All the clinical symptoms, signs and laboratory findings improved after initiating Vitamin B-12 injections. We highlight the need for low threshold to rule out Vitamin B-12 deficiency in patients presenting with symptoms and signs involving multiple body systems.